2011
DOI: 10.1038/nature10357
|View full text |Cite
|
Sign up to set email alerts
|

The ageing systemic milieu negatively regulates neurogenesis and cognitive function

Abstract: SummaryIn the central nervous system (CNS), aging results in a precipitous decline in adult neural stem/progenitor cells (NPCs) and neurogenesis, with concomitant impairments in cognitive functions1. Interestingly, such impairments can be ameliorated through systemic perturbations such as exercise1. Here, using heterochronic parabiosis we show that blood-borne factors present in the systemic milieu can inhibit or promote adult neurogenesis in an age dependent fashion in mice. Accordingly, exposing a young anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

73
1,571
9
9

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 1,528 publications
(1,698 citation statements)
references
References 32 publications
73
1,571
9
9
Order By: Relevance
“…Whether levels of these anti-ageing molecules are reduced in patients with AD, and whether they are pathophysiologically relevant to this disease, remain unknown. However, identification of these protective components could be of importance in understanding the pathogenesis of AD and in developing systemic rejuvenation therapies [68][69][70][71] .…”
Section: Blood Abnormalitiesmentioning
confidence: 99%
“…Whether levels of these anti-ageing molecules are reduced in patients with AD, and whether they are pathophysiologically relevant to this disease, remain unknown. However, identification of these protective components could be of importance in understanding the pathogenesis of AD and in developing systemic rejuvenation therapies [68][69][70][71] .…”
Section: Blood Abnormalitiesmentioning
confidence: 99%
“…For many of these chemokine proteins, there are reports that aging affect both their gene expression and protein levels (Mo et al., 2003; Whiting et al., 2015; Yung & Mo, 2003). One of these proteins, CCL11 or eotaxin has been proposed as an important factor in neurogenesis in parabiotic models of aging in mice models (Villeda et al., 2011). Our study provides supportive evidence that these class of proteins change with age in healthy older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Young and old peripheral nerves secrete CCL11 in the context of regeneration, but levels are already chronically elevated in old peripheral nerves independent of injury. Elevated CCL11 serum levels are detected in mice and humans of old age, negatively regulating neurogenesis in the CNS (Villeda et al, 2011) and interfering with nervous system functions. We demonstrated that CCL11 directly interferes with Schwann cell myelination in vitro (Figure 6) and in vivo (Figure 7)—suggesting it as an important component of the dysregulated inflammatory nerve microenvironment impairing peripheral nerve remyelination in old age; a notion supported by age‐dependent increases in CCR5 expression (Supporting information Figure S3C), a CCL11 receptor reported to be expressed by Schwann cells and upregulated upon peripheral nerve injury (Kiguchi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%